MEMBANGUN KOLABORASI DALAM PEMBUATAN PROTOTYPE CINDERAMATA “KEMBANG DUREN KULON PROGO” - Kartika Nuringsih; Nuryasman MN (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Kembang Duren Kulon Progo is a souvenir design for a tourist village in Kulon Progo. Along with the development of natural tourism in various regions, the Kalibiru destination still requires a variety of souvenirs that characterize the destination specifically. Based on sharing with the destination management during the study of the potential for sustainable tourism, the problem of souvenir needs was identified so that an idea was developed to realize souvenir work. Furthermore, collaboration with Puissance Clothing was carried out to realize the prototype. The sketch has been formed from previous activities so that the finalization to production is carried out in collaboration with the partner. In line with the tourism village development model as nature tourism, the design concept appreciates the natural wealth around the destination, namely Durian Menoreh, so the term Kulon Progo Durian Flower is used. The output is a Kembang Duren Kulon Progo T-shirt with a motif of nine durian flowers with the basic colors of black-and-white, blue-white, and red-and-white for the Independence Day edition. Collaboration provides solutions for destinations in the form of souvenir designs which in the future can be developed by the manager in various media such as mugs, drinking bottles, tumblers, cloth bags, or masks. Through the branding,